Hubungan Optimisme dengan Kecemasan akan Kematian pada Penderita Penyakit Diabetes Mellitus di Klinik Romana - Igorienni Pasaribu H; Mustika Tarigan; Maghfirah Maghfirah (Jouska: Jurnal Ilmiah Psikologi, 2022)
This study uses a correlational quantitative type aimed to determine the relationship between optimism and anxiety about death in patients with type II Diabetes Mellitus. Death anxiety is an unpleasant emotional state in the form of fear, tension, anxiety, and emotons about end of life events experienced by individuals. One of the factors that influence death anxiety is belief (optimism). Optimism is a positive and realistic way of thinking about a problem that helps improve psychological health. The sample involved in the study were 43 people taken using a purposive sampling techniqui based on the criteria; patiens with type II Diabetes Mellitus, aged 40 and over, were recorded to be actively seeking treatment at the clinic. The research data was collected using an optimism scale and a death anxiety scale tested using product moment. The results showed that there was no significant relationship between optimism and death anxiety in patients with type II Diabetes Mellitus, (rxy = 0,11 with p = 0,48 0,05). It isknown that optimism contributes 11% to be high (empirical mean = 85.81 hypothetical mean 85.50) and death anxiety is classified as high (empirical mean = 21.02 hypothetical mean = 15.00). This means in people with Diabetes Mellitus is rejected.